Introduction - Hvid, Helge (Nordic Journal of Working Life Studies, 2012)
By coincidence four of the ve articles in this issue are interconnected as they are all related to computer based work. Work which has went through major changes as a result of the IT development. Yet, they analyze very different kinds of IT work: developers and designers in the IT field, IT-based administrative work and work in call centers. The four articles all analyze changes in identity, motivation and control at work related to changing work conditions. All four articles are based on case studies and use qualitative methods. The last article takes up a very relevant theme given the present financial and economic crisis, namely the re-employment of employees who become unemployed as a result of mass layoffs (...)